Telemammography: Technical Advances Improve Patient Access in Breast Care. Issue 2 (16th January 2020) - Chung, Hannah L; Parikh, Jay R
Abstract: Screening mammography's efficacy in reducing breast cancer deaths depends on patient compliance with screening recommendations and the radiologist's interpretative skills. Reasons for suboptimal screening compliance may be multifactorial, including possible limitations in access. Additionally, while studies show experienced breast radiologists are more accurate in their mammographic interpretation, only a minority of the nation's mammograms are interpreted by breast imaging specialists. To simultaneously optimize the benefit of early breast cancer detection while minimizing the harms associated with a false positive interpretation, delivery models that help improve access to breast expertise should be considered. Telemammography is one such delivery model that may be underutilized in current practice. While radiologists and other stakeholders of healthcare have accepted teleradiology interpretation of non-mammography studies as routine, telemammography use and acceptance is less well known. In this article, we review the operational components of a telemammography practice in today's information- and technology-dependent society. Current use of telemammography and remaining potential challenges are discussed. Telemammography can improve healthcare delivery and access by bringing together patients and breast expertise. If accepted, use of telemammography can help meet Centers for Disease Control's Healthy People 2020 goals related to breast cancer.